Disaster Management: Enabling Resilience - Masys, Anthony (Lecture Notes in Social Networks, 2015)
The present work will discuss relevant theoretical frameworks and applications pertaining to enabling resilience within the risk, crisis and disaster management domain. The contributions to this book focus on resilience thinking along 4 broad themes: Urban Domain; Cyber Domain; Organizational/Social domain; and Socio-ecological domain. This book would serve as a valuable reference for courses on risk, crisis and disaster management, international development, social innovation and resilience. This will be of particular interest to those working in the risk, crisis and disaster management domain as it will provide valuable insights into enabling resilience. This book will be well positioned to inform disaster management professionals, policy makers and academics on strategies and perspectives regarding disaster resilience.